Woke up no light - Mottley, Leila, 2002- (Alfred A. Knopf, 2024)
"Woke up no light is a Black girl's saunter turned to a woman's defiant strut. These are the hymns of a new generation of poetry. Young, alive, yearning. A mouth swung open and ready to devour. A quest for home in a world that knows only wasteland and wanting. Moving in sections from "girlhood" to "neighborhood" to "falsehood" to, finally, "womanhood," these poems reckon with themes of reparations, restitution, and desire. The collection is sharp and raw, wise and rhythmic, a combination that lights up each page. From unearthing histories to searching for ways to dream of a future in a world constantly on the brink of disaster, this young poet sets forth personal and political revelation with piercing detail"--